PERCEIVING THE SACRED FEMININE: SOME THOUGHTS ON THE CYCLADIC FIGURINES AND JUNGIAN ARCHETYPES - T. V. Danylova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Without claiming to explain the meaning and purpose of the Cycladic figurines of the canonical type (FAF) in the context of the culture that created them, the author attempts to investigate the phenomenon of these ancient images and their impact on contemporary humans through the lens of Carl Gustav Jung’s theory of the collective unconscious and the archetypes. Theoretical basis. The primary meanings and purposes of the Cycladic figurines are ambiguous and incomprehensible to us. We cannot understand them in the context of their original culture. But we are able to create our own meanings: unfinished images generate an opportunity to bypass our conscious mind and to contact the unconscious. The Cycladic figurines may resonate with female archetypes in the male and female psyche, as well as symbolize the ontological primacy of creative unity of opposites, the integrity of consciousness and the unconscious. Originality. The author outlined the possible unconscious meanings generated by the Cycladic figurines for human psyche. The Cycladic figurines actualize the archetypes of the collective unconscious, such as the Great Mother, the Anima, and the Self. These ancient images can be used for introspection, art therapy, active imagination, meditation, mindfulness. Conclusions. The results show that the Cycladic figurines have had a huge impact on the artists of the 20th century and continue to influence our contemporaries due to the emotional response they evoke in the unconscious, which conceals the primordial features of the ancient mind. Laconic ancient images provide a vast space of options for human imagination. In an attempt to interpret them, we are suddenly seized and carried away into unknown depths. Archetypal images are manifested in any form – from sublime and beautiful to terrible, but they create a single space full of numinous awe and beauty. Engaging with the archetypes and revealing their hidden messages, we establish a connection between consciousness and the unconscious, between the personal and collective unconscious to achieve a deep self-awareness and inner growth.